2005
DOI: 10.2196/jmir.7.3.e27
|View full text |Cite
|
Sign up to set email alerts
|

Online Health Behavior and Disease Management Programs: Are We Ready for Them? Are They Ready for Us?

Abstract: Advancing the science and practice of health promotion and disease management on the Internet requires a systematic program of research examining the population impact of such programs. With impact described as the combination of effectiveness and participation, such research needs to include the examination of the quality and effectiveness of programs that are available to the general public, as well as descriptive and predictive knowledge about population readiness to participate in such programs.There have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 4 publications
3
58
1
Order By: Relevance
“…This is in line with other studies, where features aimed to increase websites' interactivity (personally tailored feedback) and attractiveness (such as videos) increased the time participants spent on the website (Brouwer et al, 2011;Brouwer et al, 2008;Ferney, Marshall, Eakin, & Owen, 2009). The fact that using video-tailored feedback resulted in participants spending more time on the website is an important finding of this study, as it has been demonstrated that the more time participants spent on the website, which equals more exposure to intervention content, the more likely the intervention might induce changes in health behaviors (Lewis et al, 2008;McKay et al, 2001;Schubart, Stuckey, Ganeshamoorthy, & Sciamanna, 2011;Steele et al, 2007).…”
Section: 40supporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with other studies, where features aimed to increase websites' interactivity (personally tailored feedback) and attractiveness (such as videos) increased the time participants spent on the website (Brouwer et al, 2011;Brouwer et al, 2008;Ferney, Marshall, Eakin, & Owen, 2009). The fact that using video-tailored feedback resulted in participants spending more time on the website is an important finding of this study, as it has been demonstrated that the more time participants spent on the website, which equals more exposure to intervention content, the more likely the intervention might induce changes in health behaviors (Lewis et al, 2008;McKay et al, 2001;Schubart, Stuckey, Ganeshamoorthy, & Sciamanna, 2011;Steele et al, 2007).…”
Section: 40supporting
confidence: 91%
“…However, engagement and retention problems have been reported for this type of intervention (van den Berg, Schoones, & Vliet Vlieland, 2007). Health interventions provided via the Internet are struggling with dropout rates that reach up to 40-50% (Bennett & Glasgow, 2009;Evers, Cummins, Prochaska, & Prochaska, 2005;Eysenbach, 2005). Thus, although website-delivered interventions have the potential to reach large numbers of people, this is often not achieved.…”
mentioning
confidence: 99%
“…However, the relatively low recruitment rate of 7 percent (vs 28%-40% in face-to-face recruitment models) suggests a selection bias may have played a role, supporting conjecture 2 [43][44]. However, these low recruitment rates may not be unusual for a fully online intervention and may be consistent with the finding that only 10 to 20 percent of adults are interested in an Internet-based lifestyle change at any given time [45][46]. Furthermore, the moderate depression pre/post ESs were less than those seen in treatment interventions involving therapist and discussion group contact (VETS PRE-VAIL ES = 0.45 vs Internet plus therapist contact ES = 0.93) [21,[47][48] but comparable with preventive interventions using an Internet-only approach (male adolescents ES = 0.29) [47,49].…”
Section: Discussionsupporting
confidence: 55%
“…and more than 75% met no more than two (81). IBCT is no different from any other tool for improving patients ' care, and its value depends on its goals, informational content, and appropriate patient targeting.…”
Section: Look Before You Leap (But Do Not Forget To Leap) Diabetes-fmentioning
confidence: 99%